Perspektif Orientalis tentang Hadis Nabi - Idri Idri (IAIN Ponorogo, 2011)
As the second source of Islam after the Qur’an, hadis is intresting to be studied by muslims as well as non-muslims (Orientalists). There are many differences between hadis studies according to Orientalists and Muslim scholars. The differences occur in accordance with their scientific tradition, beliefs, and points of view which are relatively dissimiliar. Muslim scholars see Hadis as the source of Islam that came from the Prophet Muhammad – peace be upon him. It is the sayings or statements, doings, and approvals of the Prophet, meanwhile according to Orientalists, hadis was made by muslim community in the first and second age of Higra. It does not the sayings, doings, or approvals of the Prophet, but the sayings of common people which later transmitted and hang up to the Prophet. This article tries to explain critcal tradition of hadis among Orientalists along with the topicts such as the history of hadis studies among Orientalists, the attitudes of Orientalists toward Islam, generally and especially hadis, the Orientalist’s points of view about sanad and matn of Hadis. The analysis of this article also describe implication of the Orientalists viewpoints to the existence and probativeness of the Prophet’s hadis.